POTENSI DAUN ASHITABA (Angelica keiskei) SEBAGAI SUMBER FITOBIOTIK DALAM PAKAN TERHADAP PRODUKSI LEMAK ABDOMINAL AYAM BROILER - Dina Oktaviana Spt; Mashur Mashur; Candra Dwi Atma; Maratun Janah; Kunti Tirta Sari (VITEK : Bidang Kedokteran Hewan, 2020)
Ashitaba leaves have many vitamins, minerals, amino acids, antioxidants, and has the potential to be a feed supplement to chicken growth. The purpose of this study was to determine the potential of Ashitaba leaf flour as a source of probiotics in feed on levels of broiler abdominal fat production. 25 DOC broilers were kept for 35 days. The treatment was the addition of Ashitaba leaf flour in basal feed with different levels ; P0 (0% Ashitaba Leaf Flour + 98% Basal Feed + 2% Filler); P1 (0.5% Ashitaba Leaf Flour + 98% Basal Feed + 1.5% Filler); P2 (1% Ashitaba Leaf Flour + 98% Basal Feed + 1% Filler); P3 (1.5% Ashitaba leaf meal + 98% Basal feed + 0.5% Filler) and; P4 (2% Ashitaba leaf flour + 98% Basal feed + 0% Filler). The data obtained were analyzed using variance and if there were significant differences it would be further tested with the Duncan Distance Test. The results showed that giving Ashitaba Leaf Flour up to a level of 2% had a significant on increasing the weight of broiler (P> 0.05) but had no significant (P> 0.05) on the weight of abdominal fat and the percentage of abdominal fat.